The Influence of Brand Image, Price, and Social Media Marketing on Car Purchase Decisions at Honda Perdana - Laelasari, Memey; Fadilah, Hamidah Fauziah; Sumawidjaja, Riyandi Nur; Mubarok, Dadan Abdul Aziz; Herlinawati, Erna (Transpublika Publisher, 2026)
The growing intensity of competition in the automotive industry has encouraged companies to more thoroughly examine marketing elements that shape consumer behaviour and purchasing decisions. At the dealership level, sales performance often experiences fluctuations across different periods, indicating that the marketing strategies implemented have not yet fully succeeded in maximising consumer purchase outcomes. This situation highlights the importance of conducting empirical research that concentrates on fundamental marketing variables. Aiming to analyze the impact of brand image, pricing, and social media marketing on car purchase decisions, this research focuses on consumers of the Honda Perdana Soreang Branch. A quantitative survey method was employed, collecting primary data through questionnaires from past customers. Analysis via multiple linear regression shows that all three variables have a positive and significant influence on purchasing decisions, both partially and simultaneously. These findings indicate that a strong brand reputation, pricing strategies aligned with consumer value perceptions, and effective utilisation of social media platforms can enhance consumer confidence in making car purchase decisions. It is expected that this study will enhance the theoretical foundations of marketing management while delivering practical recommendations to assist automotive companies in developing more effective and consumer-oriented marketing strategies.